Gamification as a learning strategy in the efl teaching - SARAIVA, Wemerson Procopio (2023)
Gamification is a methodology used to transform any content into a game in order to bring a more stressful environment that can be applied in different ways in the classroom without age restrictions. But the game must be made thinking about the target class of an end of life. the interest of students is due to this that the teacher has a crucial role, the objective is to study the student's progress within the English classroom, a methodology used for this was qualitative and descriptive research where students had a form to fill in so that the teacher can obtain information about the English level of each one of them and select among those that would serve as a reference for the students' analysis. The proven results demonstrate that the students had stress-free classes and that they felt motivated to learn significant challenges that each game had over five classes and with that their progress was in English.